The bull-roarer in history and in antiquity - Harding, J. R. (International Library of African Music, 1973)
In his article, 'Musical Instrumentation among the San (Bushmen) of the Central Kalahari1', Dr. G. T. Nurse mentions the bull-roarer and hints at its use other than as a child's toy. In this connection the following brief notes on its usage and significance may be of interest
Keywords: African Music